A Defined Medium for Cultivation and Exometabolite Profiling of Soil Bacteria - de Raad, Markus; Li, Yifan V.; Kuehl, Jennifer V.; Andeer, Peter F.; Kosina, Suzanne M.; Hendrickson, Andrew; Saichek, Nicholas R.; Golini, Amber N.; Han, La Zhen; Wang, Ying; Bowen, Benjamin P.; Deutschbauer, Adam M.; et al. (Frontiers in Microbiology, 2022)
Exometabolomics is an approach to assess how microorganisms alter their environments through the depletion and production of metabolites. It allows the examination of how soil microbes transform the small molecule metabolites within their environment, which can be used to study resource competition and cross-feeding. This approach is most powerful when used with defined media that enable tracking of all metabolites. However, microbial growth media have traditionally been developed for the isolation and growth of microorganisms but not metabolite utilization profiling through LC-MS/MS. Here, we describe the construction of a defined medium, the Northen Lab Defined Medium (NLDM), that not only supports the growth of diverse soil bacteria but also is defined and therefore suited for exometabolomic experiments. Metabolites included in NLDM were selected based on their presence in R2A medium and soil, elemental stoichiometry requirements, as well as knowledge of metabolite usage by different bacteria. We found that NLDM supported the growth of 108 of the 110 phylogenetically diverse (spanning 36 different families) soil bacterial isolates tested and all of its metabolites were trackable through LC–MS/MS analysis. These results demonstrate the viability and utility of the constructed NLDM medium for cultivating and characterizing diverse microbial isolates and communities.